STRATEGIE UCZENIA SIĘ SŁOWNICTWA – OBCOKRAJOWCY VS. UŻYTKOWNICY JĘZYKA ODZIEDZICZONEGO - Seretny, Anna (Neofilolog, 2018)
In an average Polish language intermediate class (level B1/B2) there are two types of learners; namely, heritage language learners (HLLs) and foreign language learners (FLLs). HLLs are of Polish origin and have gained partial knowledge of the language in a natural environment, unlike FLLs who have learnt Polish in a formal institutional setting and have no Polish roots whatsoever. Teachers of Polish as a foreign/second language claim (in anecdotal evidence), that HLLs speak more fluently, particularly when talking about everyday topics, and that their production sounds more native like, as it is more formulaic. HLLs are, however, perceived as poorer vocabulary learners than FLLs. The aim of the research described in this article was to find out if this phenomenon can be ascribed to the different number and/or type of vocabulary learning strategies used by learners from the two groups.